MODERN METHODS OF TEACHING BIOLOGY IN PEDAGOGICAL UNIVERSITIES - Lola Narmatovna Egamberdieva (Galaxy International Interdisciplinary Research Journal, 2023)
This article reveals modern methods of teaching biology. Many biological processes are characterized by a peculiar complexity. Multimedia animation models make it possible to form a complete picture of the biological process in the student’s mind, interactive models make it possible to "design" the process on their own, correct their mistakes, and self-learn. At the present stage of development of school education, the problem of using computer technology in the classroom is of great importance, especially in recent years.